THE STUDY OF RELATIONSHIP BETWEEN MOTIVATION TO JOINING IN REFERENCE GROUPS AND COMMUNICATION INTENSITY WITH A LEVEL CONFIDENCE OF DEVELOPING TALENT - Afny Khotiatina; Agus Naryoso, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
This research is based of the phenomenon changes the motivation when the teens will join with reference groups. They join the reference groups no longer to develop the potential that exists within them but because of a strong desire to get a popularity. The purpose of this research was to know relationship motivation joined in reference groups and the intensity of the communication with a level of confidence on the development of talent. The methods used in this research is quantitative eksplanatori by the respondent as much as 158 people out of a population of Hidayatullah Islamic HIGH SCHOOL. Data retrieval in this study using questionnaires and instruments for assisted processing program SPSS 16.0 with test reliability, validity, and the normality hypothesis. The result of this research showed positive results where there is a relationship of the motivation of joining in reference groups with a level of confidence on the development of talent and the intensity of the relationship there is also communication with the level of confidence on the development of talent. It is proved that the theory of Maslow's hierarchy and the theory of Group trusted Bales proved his righteousness.